(untitled) (Bangladesh Journal of Urology, 2020)
This prospective study has been done to compare the results of treatment of uncomplicated upper ureteral calculi by in situ ESWL and ESWL after push back. Ninety consecutive patients with single upper- ureteric stones of < 1 cm in size with no distal obstruction were selected and divided into two groups. Fifty patients in group 1 were treated by in situ ESWL while 40 patients in group 2 were treated by push back followed by ESWL. In the in situ ESWL group, 56% cases were cleared of stone otter l week of first session, 24% cases required second and 10% cases required third sessions for complete clearance of stone. Overall 90% clearance was achieved after 90 days in this group. In the ESWL after push back group, 52.5% cases were cleared of stone after- 1 week of first session, 30% cases required second and 10% cases required third sessions for complete clearance of stone. Overall 92.5% clearance was achieved after 90 days in this group. Although more clearance rate was achieved in ESWL after push back, it was not statistically significant (p>0.05). The number of average ESWL sessions required was 1.54 for stone cm and 1.77 /or stone of l crn in the in situ ESWL group, where as it was 1.46 and 1.48 respectively for stones - / cm and of 1 cm respectively in the ESWL after push back group, however this difference was not statistically significant. More shock wave and energy was needed in the in situ ESWL group than in ESWL after push back group. The mean shock wave was 1994 + 449 for in situ ESWL group and 1757.5 ± 255 for 17S117, after push back group, which was statistically very significant (p<0.01). The mean energy used was 5.07 L 0.81 in the in situ ESWL group and 4.6 0.48 in ESWL after push back group and this difference was also statistically significant (p<0.01). Post procedure complications like loin pain, noninvasive nature of ESWL has a strong appeal to the patients and physicians, and has become the first line treatment option for proximal ureteral stones. Although some urologists claim a higher success rate of ESWL after push back procedure, the invasiveness of the additional ureteral manipulation must be considered 6. On the other hand, in situ ESWL for uncomplicated upper ureteric calculi is appealing because it is noninvasive, requires no anesthesia, low morbidity, low cost and can be performed as an outpatient therapy and offers acceptable results. So, this study has been done to compare the results of treatment of uncomplicated upper ureteral calculi by in situ ESWL and ESWL after push back. Bangladesh Journal of Urology, Vol. 14, No. 2, July 2011 p.51-54